2020
DOI: 10.1016/j.jsat.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Replication of an emergency department-based recovery coaching intervention and pilot testing of pragmatic trial protocols within the context of Indiana's Opioid State Targeted Response plan

Abstract: Solving the opioid crisis requires immediate, innovative, and sustainable solutions. A number of promising strategies are being carried out by U.S. states and territories as part of their Opioid State Targeted Response (STR) plans funded through the 21st Century Cures Act, and they provide an opportunity for researchers to assess effectiveness of these interventions using pragmatic approaches. This paper describes a pilot study of Project Planned Outreach, Intervention, Naloxone, and Treatment (POINT), the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…A number of trials studied the peer support effect on drug users, especially in the emergency department [ 53 , 54 ]. Another randomized trial found that a socially focused treatment can affect change in the patient’s social network and hence increase support for abstinence, for example, an increase of one nondrinking friend in the social network is translated into a 27% increase in the probability of reporting abstinence on 90% of days or more at all follow-up visits, which extended to 15 months [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of trials studied the peer support effect on drug users, especially in the emergency department [ 53 , 54 ]. Another randomized trial found that a socially focused treatment can affect change in the patient’s social network and hence increase support for abstinence, for example, an increase of one nondrinking friend in the social network is translated into a 27% increase in the probability of reporting abstinence on 90% of days or more at all follow-up visits, which extended to 15 months [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, investigators are evaluating the effectiveness of an innovative peer support program that incorporates leadership training, mentorship, recognition, and reward systems for PSWs, coupled with automated daily supportive text messaging, which has proven effectiveness in feasibility trials involving patients with depression and alcohol use disorders [ 120 , 121 ]. Previous studies have examined the effect of PSSs in different contexts, including outpatient departments [ 122 ], emergency departments [ 53 , 54 ], community mental health clinics [ 123 , 124 ], and inpatient sites [ 125 ]. On the contrary, the EPSS study focuses on patients who have been discharged from acute care hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…Peers were able to build rapport based on commonalities and promote harm reduction efforts in the community. Studies conducted in emergency departments and clinical settings in the US and in other contexts globally have similarly reflected the acceptability and potential for peers in harm reduction and recovery support services, including for reduction of use, decreased risk behaviors, and improved quality of life [26,[60][61][62][63][64][65][66][67]. Particularly considering some stigmatizing interactions with health care workers, as one client noted above, individuals may be better able to share experiences and address underlying factors contributing to problematic substance use when working with a PRC.…”
Section: Discussionmentioning
confidence: 99%
“…The program is also staffed with a DATA‐waivered nurse practitioner who provides buprenorphine, a licensed chemical dependency counselor who provides substance abuse counseling, and peer recovery coaches who provide support groups and regular check‐ins on participants of the program, and preliminary results suggest that 88% of people are retained in treatment at 30 days 45,46 . Programs such as EPICC (Engaging Patients in Care Coordination) in St. Louis, the RIMO (Recovery Initiation and Management After Overdose) intervention in Chicago, Project POINT (Planned Outreach, Intervention, Naloxone, and Treatment) in Indiana, and AnchorED (Anchor Recovery Center and Emergency Department) in Rhode Island also leverage the lived experience of peer recovery coaches within their programs, because coaches relate to the common challenges and barriers to sustaining treatment 47–50 …”
Section: Resultsmentioning
confidence: 99%